IDENTIFIKASI URBAN HEAT ISLAND (UHI) MELALUI TEKNOLOGI PENGINDERAAN JAUH DI PROVINSI DKJ JAKARTA TAHUN 2023 - Mujahid, Hakim Ikhwan; Irawan, Listyo Yudha (Jurnal Tanah dan Sumberdaya Lahan, 2025)
One of the impacts of the rampant urbanization is the rising phenomenon of Urban Heat Island (UHI). This phenomenon occurs when the temperature in urban areas is higher than in the surrounding areas that are less developed (rural). The research was conducted in DKJ Jakarta Province, namely East Jakarta City, South Jakarta City, North Jakarta City, Central Jakarta City, and West Jakarta City. This study aimed to analyze the highest and lowest distribution of UHI based on the Land Surface Temperature (LST) algorithm and using the overlay method. Data were collected through literature study and analysis of Landsat 8 level 2 satellite imagery collection 2 Tier 1 OLI 2. The results of the study showed that high urbanization (population density) affected the average value of CSI to increase so that it was directly proportional to UHI. The non-UHI intensity range ranged from -4 oC to 0 oC, while the areas experiencing UHI had an intensity range ranging from ±0oC to 8.6oC. The city with the highest intensity was estimated to be in the East Jakarta City area while the lowest was in the Central Jakarta area.